(untitled) (Cultura de los cuidados, 2021)
Reconfigured reflection of the lecture presented and entitled “Lessons from Florence Nightingale in times of Covid-19” at the I Congreso Virtual Comemoriación del Bicentenario del Nascimento by Florence Nightingale (1820-2020), from 25 to 27 May 2020, in Santa Cruz de Tenerife (Spain). Therefore, these are some lessons left by the leader of modern nursing applied in the present time of the Covid-19 pandemic, when attitudes possibly neglected by public, private and health authorities were left to second and / or third plans from a local outbreak to a pandemic